The Weight of Product Quality and Service Quality on Customer Satisfpretense of PT. Tigabelas Pilar Mandiri in South Jakarta - Siti Mariam; Siti Fatimah; Atong Soekirman (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
This investigation aims to examine and anatomize the weight of product quality and service quality variables on customer satisfpretense at PT Tigabelas Pilar Mandiri in South Jakarta. This research usual multiple linear regression method where the data was cured by SPSS program. The sample consisted of 61 respondents who were customers of PT Tigabelas Pilar Mandiri in 2020. The instrument usual to collect data was a structured questionnaire with a Likert scale consisting of 32 questions that were composed based on indicators and measurement derived from every variproof. The results showed that: (1) Product Quality impresss Customer Satisfpretense by 57.2%; (2) Service Quality impresss Customer Satisfpretense by 33.3%; (3) Product Quality and Service Quality synchronously impress Customer Satisfpretense by 57.8%.